Migration of fragments into the spinal canal after intervertebral polyethylene glycol implantation: an extremely rare adverse effect - Akgun, Bekir; Ozturk, Sait; Cakin, Hakan; Kaplan, Metin (Amer Assoc Neurological Surgeons, 2014)
Percutaneous intervertebral hydrogel (polyethylene glycol) implantation is a current treatment procedure that aims to restore hydration of a degenerated disc. There have been a few studies that claim that polyethylene glycol is successful for pain relief as the intervertebral space restores its hydration and elasticity. This procedure is reported to be indicated for discogenic low-back pain and mild radicular pain as it contributes to disc restoration. In this report, the authors describe the case of a 43-year-old woman who was admitted with low-back and right leg pain. Muscle strength in dorsifiexion of the right ankle and right toe was 3/5. The patient had undergone hydrogel implantation for L4-5 intervertebral disc restoration 2 days prior to presentation. There was a significant increase in the patient's complaints after hydrogel implantation, and acute weakness in the right ankle and toe had developed. Magnetic resonance imaging of the lumbar vertebrae, which was performed before the hydrogel implantation, showed a significant narrowing of the L4-5 disc space height, and a disc herniation that extended to the right neural foramen and caused compression of the dural sac. The patient underwent surgery immediately. The sequestered disc fragment that caused a prominent stenosis in the spinal canal, as well as hydrogel fragments, was removed. There was an improvement in the patient's complaints and motor deficit postoperatively. In this paper, a very rare complication is reported. In patients who have increased pain after intervertebral hydrogel implantation and who develop a neurological deficit, the migration of the applied material into the spinal canal should be considered.
Keywords: hydrogel; lumbar disc herniation; polyethylene glycol; minimally invasive approach